FROM KINGDOMS TO KINGDOM: A HISTORICAL APPRAISAL OF THE CHIEFTAINCY INSTITUTION IN OKALAND SOUTH-WEST NIGERIA - Ogunode, Sunday Abraham (European Scientific Journal, ESJ, 2012)
The chieftaincy institution is one of the cultural assets and peculiarities of the Yoruba people, which constitutes important roots of relationship and co-existence among the Yoruba kingdoms, especially in the pre- colonial times. Chieftaincy is an indigenous system of governance with executive, judicial, and legislative powers. Since the pre-colonial times up till this present time, the chieftaincy institution has come to serve two major functions, which can conveniently be divided into statutory and non- statutory. While the statutory functions include settlement of chieftaincy disputes and the codification of customary laws, the non- statutory functions are reflected in their efforts towards the socio- economic development of the communities where such exist. In pre-colonial Okaland, a form of village government headed by hereditary chiefs and elders and strengthened by the age grades was evolved in the fifteen quarters that make up the present day Oka kingdom. Families and lineages made up the quarters which occupied specific parts of the village. The family was the smallest unit of administration. By 1900, the traditional political structure of Oka was altered with the effect that the fifteen mini kingdoms that had hitherto enjoyed virtual independence under their respective traditional ruler were brought under one centralised administration. This period marked the emergence of the Olubaka as the paramount ruler of the Oka kingdom. Essentially, the paper seeks to argue that the emergence of the Olubaka marked the beginning of a comprehensive socio-political system that has endured and has continued to form the basis of validation.